2020
DOI: 10.1101/2020.04.01.021188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lessons from the analysis of TAD boundary deletions in normal population

Abstract: Topologically Associating Domains (TAD)-boundaries induce spatial constraints, allowing interaction between regulatory elements and promoters only within their TAD. Their disruption could lead to disease, through gene-expression deregulation. This mechanism has been shown in only a relatively low number of diseases and a relatively low proportion of patients, raising the possibility of TAD boundary disruption without phenotypical consequence. We investigated, therefore, the occurrence of TAD boundaries disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, while a large number of disease-related copy number variations (CNVs) are predicted to affect TAD structure [14,15], a whole-genome analysis in over 2500 cancer genomes identified almost 300 000 TAD disruptions, of which only 14% led to a change in gene expression [16]. Similarly, a recent study found that 41% of TADs across 36 datasets had at least one boundary disrupted by a common CNV classified as (likely) benign [17], indicating that TAD boundary deletion without a strong effect on the phenotype is widespread. Given the small numbers of diseases associated with a TAD boundary disruption, it appears that either such disruptions are too rare to be identified, too disruptive to produce a viable embryo, or not important enough to cause a detectable phenotype.…”
Section: Structural Variation Leading To Enhancer Mistargetingmentioning
confidence: 99%
“…However, while a large number of disease-related copy number variations (CNVs) are predicted to affect TAD structure [14,15], a whole-genome analysis in over 2500 cancer genomes identified almost 300 000 TAD disruptions, of which only 14% led to a change in gene expression [16]. Similarly, a recent study found that 41% of TADs across 36 datasets had at least one boundary disrupted by a common CNV classified as (likely) benign [17], indicating that TAD boundary deletion without a strong effect on the phenotype is widespread. Given the small numbers of diseases associated with a TAD boundary disruption, it appears that either such disruptions are too rare to be identified, too disruptive to produce a viable embryo, or not important enough to cause a detectable phenotype.…”
Section: Structural Variation Leading To Enhancer Mistargetingmentioning
confidence: 99%
“…For example, the disruption of specificT A D boundaries or insulated structures and consequently unexpected enhancer-promoter interactions can induce aberrant gene expression, especially that of diseaserelated genes [7][8][9]. Surprisingly, the global loss of TAD structure via depletion of cohesin leads to significant changes of expression level of only about 1000 genes [10], indicating a limited role of TAD structure in regulating gene transcription [11]. Moreover, multiplex promoter-centered chromatin interactions such as promoter-promoter interactions of different genes have been widely investigated using ChIA-PET targeting on RNA polymerase II (RNAPII) and are thought to play a vital role in transcription regulation [12].…”
Section: Introductionmentioning
confidence: 99%